Khandbal. Svetoven festival na mladezhta i studentite, Sofiya, 1968 (1968)
Male volleyball player lunging Poster advertising World Festival of Youth and Students, held in Sofia, 1968. Original title: Хандбал. Световен фестивал на младежта и студентите, София, 1968 PO-1124